The Effect of the Cooperative Make a Match Model Assisted by Flipbook on Students’ Beginning Reading Ability - Zalfa Luthfiyah; Feby Inggriyani; Dheni Harmaen (Journal Informatic, Education and Management (JIEM), 2026)
This study aimed to determine the effect of the cooperative Make a Match model assisted by Flipbook on the beginning reading ability of first-grade students at SDN 068 Sindanglaya. The background was the low reading literacy among Indonesian students based on PISA 2018 (ranked 74th out of 79 countries) and the low beginning reading ability in grade I at SDN 068 Sindanglaya (average 66.7). The research method used was quantitative quasi-experiment with a nonequivalent control group design. The sample consisted of 56 first-grade students: 28 students in class 1A as the experimental class and 28 students in class 1B as the control class. Data collection techniques included tests (pretest and posttest), observation, and documentation. The results showed that the Make a Match model assisted by Flipbook had a large effect on improving beginning reading ability. The experimental class average score increased from a pretest of 65.75 to a posttest of 85.75, while the control class increased from 64.47 to 78.42. The N-Gain test showed an increase of 70% (high) in the experimental class and 61% (moderate) in the control class. The effect size test yielded a value of d=1.00, categorized as a high effect. In conclusion, this learning model is effective in improving students’ beginning reading ability.